Temporal and Spatial Patterns of Groundwater Recharge Across a Small Watershed in the California Sierra Nevada Mountains - Meadows, Christina; Hagedorn, Benjamin (Frontiers in Water, 2022)
Mountain-block groundwater recharge is a crucial freshwater source in arid to semiarid watersheds worldwide; yet its quantification is difficult due to (1) hydrogeological heterogeneities especially in bedrock-dominated regimes, (2) drastic altitudinal ranges in climate, land use and land cover, and (3) mixing with deep groundwater derived from adjacent basins (i.e., interbasin groundwater flow). This study tests the utility of soil water balance (SWB) modeling to quantify mountain-block groundwater recharge in the South Fork Tule River watershed in the California Sierra Nevada Mountains. This 1,018 km2 watershed has been instrumented with 3 USGS stream gages that allow for the development of a refined recharge (i.e., baseflow) calibration dataset via optimized hydrograph separation. The SWB model was used to compute groundwater recharge and other water balance components at a daily time step using a 30 m grid cell size for a 40-year (1980 – 2019) study period. Mean annual recharge and runoff were estimated at 3.0 m3/s and 1.2 m3/s, respectively, with modified Nash Sutcliffe Efficiency indices of 0.61 between baseflow and SWB-derived recharge, and 0.90 between hydrograph separation- and SWB-derived runoff. There is a strong correlation between annual recharge and rainfall (Pearson R = 0.99, p <0.001) which attests to short residence times in the unsaturated zone and the immediate impact of droughts in 1990, 1999, and 2013. Parameter sensitivity analyses reveal a persistent overprediction of recharge over baseflow that is particularly pronounced in the upper reaches of the watershed. This is likely related to the SWB model only considering soil characteristics at the surface and not simulating the fate of potential recharge below the root zone where it may be impeded from reaching the aquifer by shallow, impermeable bedrock. This limitation should be considered carefully for future water supply projections in this and comparable bedrock-dominated settings.